Statistical note: disaggregating Bhutan’s MPI 2017 by disability status - Pinilla-Roncancio, M; Alkire, S (Oxford Poverty and Human Development Initiative, 2018)
Since 2010, Bhutan has used a Multidimensional Poverty Index (MPI) alongside consumption poverty to measure and fight poverty in all its forms and dimensions. Bhutan’s National MPI was updated on 2012 and 2017 using the Bhutan Living Standards Survey (BLSS). In 2017, the BLSS questionnaire included questions on disability status. This statistical note shows different ways by which the MPI can be disaggregated using the available information. Each way is implemented, and the results analysed. Thus, by presenting worked out empirical examples, we hope to contribute to the evolving methodological discussions of how best to disaggregate poverty measures including the MPI by disability status. In addition, we hope to contribute to robust and detailed understanding in Bhutan of the relationship between poverty and disability status, hence to inform policies that seek to address both. However, survey data are limited, and so, very importantly, we also advise re-running these results with the 2017 census data for a more precise picture. It is hoped this note will provide some structure for a census-based analysis.